ALIRAN BAHAN ORGANIK PADA SAWAH PADI ORGANIK DI DUSUN JAYAN DESA KEBONAGUNG KEC. IMOGIRI KAB. BANTUL D.I. YOGYAKARTA - Arif Anshori; Bambang Hendro Sunarminto; Eko Haryono (Caraka Tani: Journal of Sustainable Agriculture, 2016)
Organic farming uses natural resources to improve the health and productivity of soil and plants. Nutrients are lost or transported through crops, erosion, leaching and volatilization must be replaced naturally and through the return of organic matter. This research aims to study the conditions of organic rice fields, specifically in terms of organic matter flow, in Jayan Kebonagung Imogiri Bantul. The organic rice field data obtained from interviews and archive farmers. The results indicate that the organic rice field in Jayan under a transition from conventional to organic rice field. Dose of organic fertilizer 10 tons/ha were given during the transition period. Organic fertilizer 5-10 tons/ha have been giving during the organic rice fields. Returns organic matter to agricultural land through land-crop-land, land-plant-livestock-land and land-crop-livestock-biogas-land. Manure, weeds and paddy field plants, crop waste, waste from agricultural products processing and non-agricultural organic wastes involved in the flow of organic matter. Farmers monitor the health and productivity of soil and plants as the basis in the management of organic rice field.